METHODOLOGICAL WAYS AND METHODS OF IMPROVING THE PROCESSES OF PREPARING FUTURE TEACHERS FOR INNOVATIVE PEDAGOGICAL ACTIVITIES - Zaripova Matluba Kulfitdinovna (European International Journal of Multidisciplinary Research and Management Studies, 2024)
The article discusses the ways and means of improving the process of preparing future teachers for innovative pedagogical activity. explores the system of improving training processes. An innovative approach also outlines ways to achieve this goal using information gathering, independent analysis of perceived information, independent expression of ideas and best (best) methods in the short term.